Health care reform in Croatia: for better or for worse? - Chen, M S (1998)
Along with the rest of Central and Eastern Europe, Croatia has begun to dismantle its long-standing socialist health care system and to replace it with a market-based approach. Marketization's advocates maintain that the market will bring efficiency and quality to the Croatian health care system. Nevertheless, data from consumer surveys and official statistics reflect the reform's hidden costs: limited access to care, heightened costs, growing inequality, and the deemphasis of preventive and proactive care in favor of costly therapeutic medicine.